ANALISIS SENTIMEN TERHADAP PENGGUNAAN APLIKASI MERDEKA MENGAJAR DI GOOGLE PLAY STORE - Farhan, Muhammad; Ramayuda, Muhammad Davin; Ruldeviyani, Yova (Universitas Nusa Cendana, 2024)
To provide a solution to the learning loss that has occurred in the education sector in Indonesia since the COVID-19 pandemic, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) released the